Створення навчального контенту з використанням технології VR, на Unreal Engine - Винокуров, Д. М. (ХНУРЕ, 2023)
Unreal Engine is one of the most popular and powerful tools for developing VR applications. Its use can help in creating high-quality and realistic virtual learning environments. Using Unreal Engine also allows developers to create interactive and dynamic virtual environments, which will allow students to gain deeper and more meaningful knowledge
Keywords: навчальний контент